2014
DOI: 10.1007/s10764-014-9768-2
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Abundance of the World's Smallest Primate, Microcebus berthae, in Central Western Madagascar

Abstract: The distribution of most recently discovered or described lemur species remains poorly known, but many appear to have small geographical ranges, making them vulnerable to extinction. Research can contribute to future conservation actions on behalf of these species by providing accurate information on local distribution and abundance. The distribution of the world’s smallest primate, the endangered Madame Berthe’s mouse lemur (Microcebus berthae), is limited to the Menabe Central region of western Madagascar. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 55 publications
(83 reference statements)
1
32
0
Order By: Relevance
“…Commonly in wildlife studies, estimation is done using capture–recapture or distance sampling (Malone et al. , Schäffler & Kappeler ; see Appendix S1).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Commonly in wildlife studies, estimation is done using capture–recapture or distance sampling (Malone et al. , Schäffler & Kappeler ; see Appendix S1).…”
Section: Methodsmentioning
confidence: 99%
“…Robust estimation of abundance or density of wild animal populations almost always requires the consideration that individuals within a sampling area will go undetected (Nichols 1992, Anderson 2001. Commonly in wildlife studies, estimation is done using capture-recapture or distance sampling (Malone et al 2013, Schäffler & Kappeler 2014; see Appendix S1). For studies conducted prior to recent species designations, we updated the species in the study to reflect the most recent taxonomy if possible.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This world’s smallest primate (ca. 30 g) is endemic to the dry forests of the Menabe region in western Madagascar (Schmid and Kappeler 1994; Ganzhorn et al 2001; Schäffler and Kappeler 2014), which has recently been identified as a priority site for conservation (Schwitzer et al 2013a). The distribution of M. berthae is restricted to an area of less than 810 km 2 within two forest fragments and a narrow corridor connecting them (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…While the total number of species is lower in the dry than in the humid forests, species richness is exceptionally high by global comparison with other dry forests [39]. Madagascar's dry forests harbor several locally endemic vertebrate species such as Madame Berthe's mouse lemur (Microcebus berthae), the giant jumping rat (Hypogeomys antimena), the narrow-striped mongoose (Mungotictis decemlineata), and plenty of other endangered species [65][66][67][68]. M. berthae, the smallest primate in the world, is particularly vulnerable to anthropogenic disturbances and restricted to core habitats of this biome [66,69,70].…”
Section: Regional Focus Area: the Dry Deciduous Forests Of Western Mamentioning
confidence: 99%